Perlindungan hukum kreditor yang memegang hak tanggungan dalam kepailitan - Mukhamad Khabib Risvian; Hanif Nur Widhiyanti; Reka Dewantara (University of Merdeka Malang, 2022)
The purpose of this paper is to overcome future problems, Law No. 4 of 1996 concerning Mortgage on Land and Objects Related to Land and Law No. 37 of 2004 concerning Bankruptcy and Postponement of Obligation to Pay Debts. Preventive and Repressive Legal Protection actions, however, a problem or conflict of law arises which regulates the time limit which is the source of problems between the Mortgage Law and the Bankruptcy Law, thus confusing stakeholders. The Bankruptcy Law provides a time limit of 2 months or 90 (days) after the bankruptcy decision is given and must be given to the Curator. but it is felt that it does not provide sufficient time for the Creditor of the Mortgage Holder. Because the creditor rights holders have protected their rights by the Mortgage Law which is written in article 21 of the Mortgage Law. Within 2 months, it does not mean that the creditor has to complete the execution, but within that period the creditor has started the execution process. due to the process that must be passed by the Mortgage Holder to sell the Mortgage Object.How to cite item: Risvian, MK., Widhiyanti, HN Dewantara, R (2022). Perlindungan hukum kreditor yang memegang hak tanggungan dalam kepailitan. Jurnal Cakrawala Hukum, 13(1). doi:10.26905/idjch.v13i1.7438.